2011
DOI: 10.1530/rep-10-0400
|View full text |Cite
|
Sign up to set email alerts
|

Specific transgenerational imprinting effects of the endocrine disruptor methoxychlor on male gametes

Abstract: Endocrine-disrupting chemicals (EDCs), among which methoxychlor (MXC), have been reported to affect the male reproductive system. This study evaluates the possible deleterious effects of MXC on imprinted genes. After administration of the chemical in adult male mice or in pregnant mice we analyzed by pyrosequencing possible methylation defects in two paternally imprinted (H19 and Meg3 (Gtl2)) and three maternally imprinted (Mest (Peg1), Snrpn, and Peg3) genes in the sperm and in the tail, liver, and skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…Four of these miRNAs (hsa-miR-146b-5p, hsamiR-509-5p, hsa-miR-519d and hsa-miR-652) have already been shown to be altered in the testes, seminal plasma and/or semen environmental toxins and factors) can induce harmful phenotypes in the descendants of exposed individuals. [6][7][8][9][10][11][12][13][14] Although the mechanisms underlying transmission of environmentallyinduced phenotypes through generations are not well understood, epigenetic changes within the germ line appear to play a central role. The association of DNA methylation with environmental exposures and heritable phenotypes has been widely established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of these miRNAs (hsa-miR-146b-5p, hsamiR-509-5p, hsa-miR-519d and hsa-miR-652) have already been shown to be altered in the testes, seminal plasma and/or semen environmental toxins and factors) can induce harmful phenotypes in the descendants of exposed individuals. [6][7][8][9][10][11][12][13][14] Although the mechanisms underlying transmission of environmentallyinduced phenotypes through generations are not well understood, epigenetic changes within the germ line appear to play a central role. The association of DNA methylation with environmental exposures and heritable phenotypes has been widely established.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Such multigenerational toxicity has been observed following exposure to other environmental chemicals and environmental factors such as nutrition and stress. [8][9][10][11][12][13][14] Epidemiological studies suggest that this phenomenon may also occur in human populations. [15][16][17][18][19] recent work has suggested that environmental chemicals, including those contained in cigarette smoke, can have adverse effects on the exposed individuals as well as their future progeny.…”
Section: Introductionmentioning
confidence: 99%
“…Poplinski et al determined that low sperm counts were clearly associated with Igf2 ⁄ H19 ICR1 hypomethylation and, even stronger, with Mest hypermethylation and idiopathic male infertility is strongly associated with imprinting defects at Igf2 ⁄ H19 ICR1 and Mest, with aberrant Mest methylation being a strong indicator for sperm quality (Poplinski et al, 2010). Stouder and Paoloni-Giacobino's studies using the xenoestrogen vinclozolin (Stouder and Paoloni-Giacobino, 2010) and methoxychlor (Stouder and Paoloni-Giacobino, 2011) have also shown changes in sperm imprinted genes that can be maintained up to the F2 generation. Indeed, methylation defects in the maternally http://www.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that endocrine disrupting chemicals are implicated in epigenetic programming and DNA methylation (McLachlan, 2001;Skinner & Anway, 2005). Indeed, hypermethylation found in several genes in the sperm DNA (i. a. Mest, Snrpn, Peg1 and Peg3) was accompanied by the reduction of semen quality (Stouder & Paoloni-Giacobino, 2010). These changes may be heritable, if they occur during certain stages of development (Crews & McLachlan, 2006).…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%